The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10875-016-0327-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Pharmacokinetics of a Novel Human Immune Globulin Subcutaneous, 20 % in Patients with Primary Immunodeficiency Diseases in North America

Abstract: Patients with primary immunodeficiency disease (PIDD) typically require life-long intravenous (IV) or subcutaneous (SC) immunoglobulin (Ig) replacement therapy to prevent recurrent infections. The efficacy, safety, and pharmacokinetics of a highly concentrated (20 %) Ig preparation for SC administration (IGSC 20 %) were evaluated in a prospective trial in patients with PIDD. A total of 74 patients (aged 3–83 years) received 4327 IGSC 20 % infusions over a median of 380.5 days. The rate of validated serious bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
120
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(148 citation statements)
references
References 32 publications
(48 reference statements)
27
120
1
Order By: Relevance
“…This is in contrast to conventional subcutaneous infusions, in which hyaluronan limits the permeability of the ECM, and the deliverable volume of drug that can be infused in a single site. The volume of conventional SCIG infusions has been limited to 20-60 ml/site depending on the SCIG formulation [21,22], necessitating frequent infusions and the use of multiple infusion sites because infusion of larger volumes resulted in significant induration, reduced absorption of IgG and pain. Preclinical studies have demonstrated that rHuPH20 is fast acting and safe.…”
Section: Recombinant Human Hyaluronidasementioning
confidence: 99%
“…This is in contrast to conventional subcutaneous infusions, in which hyaluronan limits the permeability of the ECM, and the deliverable volume of drug that can be infused in a single site. The volume of conventional SCIG infusions has been limited to 20-60 ml/site depending on the SCIG formulation [21,22], necessitating frequent infusions and the use of multiple infusion sites because infusion of larger volumes resulted in significant induration, reduced absorption of IgG and pain. Preclinical studies have demonstrated that rHuPH20 is fast acting and safe.…”
Section: Recombinant Human Hyaluronidasementioning
confidence: 99%
“…We welcome the recommendation to standardize the collection of study data to allow for more straightforward data comparisons. However, our comparative discussion made no assertion of superiority and instead stated that IG20Gly treatment was well tolerated, despite the higher infusion rates and volumes per site than those previously reported with other subcutaneous IG products [ 2 ]. The discussion of manufacturing processes, excipients, and infusion supplies in the Suez et al publication was in reference to reasons the high infusion rates and volumes up to 60 mL/h/site and 60 mL/site, respectively, were achievable with IG20Gly.…”
mentioning
confidence: 71%
“…In the recent letter to the editor, “Assessment of Local Adverse Reactions to Subcutaneous Immunoglobulin (SCIG) in Clinical Trials” [ 1 ], Ballow et al discuss the inappropriateness of making comparisons of adverse event (AE) and tolerability data from different clinical trials of subcutaneous immunoglobulins (IGs) unless the products are studied contemporaneously within the same study using the same methodology, the same investigators, and the same patient populations. The authors conclude that “given the current difficulties in standardizing methodologies across sites and studies, comparisons of tolerability of different products in reported clinical trials should be avoided.” Their letter focuses on the recent phase 3 clinical trial publication of IG20Gly (Cuvitru®, SCIG 20%, Baxalta US Inc., Westlake Village, CA, USA) by Suez et al, which reports the infusion administration parameters and rates of AEs, and discusses the results within the framework of reported data for other available subcutaneous IG products [ 2 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the drawbacks of multiple site injections and the limitations of volume per infusion, a 20% IgG product containing L-proline as a stabilizing agent (Hizentra) was introduced in 2010 (35). In 2016, based on a phase II/III study in PID (36), the glycine-stabilized 20% IgG product Cuvitru was approved by the Food and Drug Administration. These products are only for s.c. use and have the advantage of delivering a higher dose of Ig in a lower volume.…”
Section: Evolution Of Current Ivig Preparationsmentioning
confidence: 99%